Pengembangan Sistem Internet Of Things (IOT) dengan LoRa (Long Range) dan Energi Surya untuk Deteksi Otomatis Kebakaran Hutan dan Lahan - ijra, Zul Ijra Saryendy; Unik, Mitra (Universitas Muhammadiyah Riau, 2024)
Forest and land fires in Riau Province are a serious problem and can cause losses to humans and nature. It is necessary to design an Internet of Things (IoT)-based land and forest fire detection device using an independent power supply energy source. This device is equipped with DHT11 temperature sensor, MQ2 smoke sensor, and flame sensor, as well as LoRa SX276 module as data transmission media. The system utilizes IoT technology to monitor real-time environmental conditions and provide a quick response to potential fires. A standalone power supply energy source is implemented to increase the independence of the device, so that it can operate effectively in emergency situations. The LoRa SX276 module is used as a data transmission medium to enable remote communication and ensure device connectivity with the control center. Device testing was conducted through simulated fire scenarios to evaluate its performance in detecting high temperature, smoke, and fire, as well as the reliability of data transmission over the LoRa network. The results show that the device successfully detects fires with a high level of reliability and is able to transmit data efficiently over the LoRa network. The contribution of this research is the provision of an advanced and reliable fire detection solution using IoT technology and self-sustaining energy sources, with the ability to transmit data over long distances via LoRa modules.